Role of High Schools in Undocumented Students’ College Choice - Nienhusser, H. Kenny (Education Policy Analysis Archives, 2013)
In recent years, some states in the United States have enacted policies that grant some higher education benefits—primarily in-state resident tuition eligibility—to certain undocumented students. While in existence since 2001, little is known of the role of high school institutional agents in implementing such policies. This study describes the efforts of seven New York City high schools to educate their undocumented students about such educational benefits within their college choice process. It details five categories of activities that institutional agents developed to address undocumented students’ college choice needs. These college choice activities included: one-on-one counseling, presentations, outreach, scholarship, and curriculum. This study also examined the effects of institutional demographics on the process of educating undocumented students about their college choice. It discovered that those high schools that had higher percentages of undocumented students had a greater number of college choice activities and had organized their implementation in such a way as to make information more available to this student population. This article concludes with a section that is devoted to implications for research and practice.